Analyzing Dictation Errors in Arabic Writing: Identifying Causes and Strategies for Improvement among Senior High School, Medan - Nasution, Zakiah Mardiah; Al Rasyid, Harun (Universitas Yudharta Pasuruan, 2025)
This study is based on the students’ low ability to write Arabic vocabulary correctly, particularly in the aspect of imlā’.Many tenth-grade students at MAS YASPI Labuhan Deli Medan still make basic writing errors in letters, harakat, and word forms, indicating a gap between expected vocabulary mastery and actual performance. The main objective of this study is to analyze the types of imla’ errors made by students, identify the causes, and formulate appropriate teaching strategies to reduce these errors. This research employed a qualitative descriptive method with a case study design. The subjects consisted of 20 tenth-grade students. Data were collected through written tests, interviews, and documentation, and analyzed using identification, classification, interpretation, and error analysis techniques. The findings reveal eight categories of imlā’’ errors, with the most common being letter substitution and the omission or addition of letters. Contributing factors include limited understanding of imla’ rules, lack of writing practice, and less supportive teaching methods. The study recommends strategies such as applying imlā’ istimā‘ī and imlā’ manẓūr methods, along with strengthening students’ understanding of writing rules and focused writing practice, as contributions to improve Arabic writing instruction.